Starclose SE® hemostasis after 6F direct antegrade superficial femoral artery access distal to the femoral head for peripheral endovascular procedures in obese patients - Stavros Spiliopoulos; Panagiotis Kitrou; Nikolaos Christeas; Dimitris Karnabatidis (Diagnostic and Interventional Radiology, 2016)

(untitled)
PURPOSE:Direct superficial femoral artery (SFA) antegrade puncture is a valid alternative to common femoral artery (CFA) access for peripheral vascular interventions. Data investigating vascular closure device (VCD) hemostasis of distant SFA 6F access are limited. We aimed to investigate the safety and effectiveness of the Starclose SE® VCD for hemostasis, following direct 6F antegrade SFA access distal to the femoral head.METHODS:This prospective, single-center study included patients who were not suitable for CFA puncture and were scheduled to undergo peripheral endovascular interventions using direct antegrade SFA 6F access, at least 2 cm below the inferior edge of femoral head. Hemostasis was obtained with the Starclose SE® VCD (Abbott Laboratories). Primary endpoints were successful hemostasis rate and periprocedural (30-day) major complication rate. Secondary endpoint was the rate of minor complications. Clinical and Doppler ultrasound follow-up was performed at discharge and at one month.RESULTS:Between September 2014 and August 2015, a total of 30 patients (21 male; 70.0%) with a mean body mass index of 41.2 kg/m2 were enrolled. Mean age was 72±9 years (range, 67–88 years). Most patients suffered from critical limb ischemia (87.1%) and diabetes (61.3%). Calcifications were present in eight cases (26.6%). Reason for direct SFA puncture was obesity (100%). Successful hemostasis was achieved in 100% of the cases. No major complications were noted after one-month follow-up. Minor complications included two <5 cm hematomas (6.6%) not necessitating treatment.CONCLUSION:In this prospective study, Starclose SE® VCD was safe and effective for hemostasis of antegrade direct SFA puncture. Uncomplicated hemostasis was achieved even in cases of puncturing 2 to 7 cm below the inferior edge of the femoral head.